Serum bilirubin at 24 h of life birth as a predictor of significant hyperbilirubinemia in preterm neonates - Tamanna Choudhary,; Harish Kumar Mourya,; Saroj Mourya,; Mahipal Pabra,; Rajesh Kanwar,; Mohan Makwana,; Monit Kumar Goyal,; Pokar Chand, (Asian Journal of Medical Sciences, 2024)
Background: As hyperbilirubinemia is one of the key contributors to brain damage and is crucial to identify those instances that are at risk as it is more prevalent and severe among the preterms. Many studies are available in the literature for terms babies but there is paucity of data for pre terms. Aims and Objectives: The aim of this study was to assess serum bilirubin at 24 h of live birth as a indicator of significant hyperbilirubinemia in preterm neonates. Materials and Methods: It was a prospective observational study conducted in the department of pediatrics of tertiary care center, Jodhpur on 150 preterms born within 33–36 weeks 6 days after considering the exclusion criteria in the study. Area under the receiver operating characteristic (ROC) curve was used to identify significant hyperbilirubinemia within 1 week of life, along with it the cutoff value of total serum bilirubin (TSB) at 24 h of life was calculated. Results: A total of 150 enrolled preterm newborns were followed up. TSB at 24 h of life was proved to be significant using the ROC curve, where area under the curve is 0.96 which was statistically significant. Among 150 preterms, 70 newborns with TSB >4.2 mg/dL developed jaundice, and 65 babies (98.48%) required phototherapy. Hence, preterms with TSB >4.2 mg/dL have a significant risk of developing hyperbilirubinemia. (Sensitivity: 98.48%, specificity: 94.05%, negative predictive value: 98.75%, and positive predictive value: 92.86%). Conclusion: TSB for preterms at 24 h of life can support to predict the significant hyperbilirubinemia successfully. Preterms with cutoff value of serum bilirubin level >4.2 mg/dL are observed to be more prone to develop significant hyperbilirubinemia requiring appropriate intervention at the earliest.